Exploring agro-morphological diversity of Algerian hot pepper (Capsicum annuum L.) accessions using multivariate statistics - Bedjaoui, Hanane; Boulelouah, Nadia; Seghir Mehaoua, Mohamed; Baississe, Salima (Emirates Journal of Food and Agriculture, 2022)
Pepper is an inevitable constituent in the diets of Algerian population. Unfortunately, the local landraces are endangered by both genetic erosion and pollution. This study aimed to perform agro-morphological characterization of hot peppers (Capsicum annuum L.) accessions. Twenty one accessions collected from the east and south of Algeria were evaluated for 24 quantitative and 38 qualitative morphological characters under green-house conditions. The trial was conducted in a Randomized Complete Block Design (RCBD), with four replicates at the experimental station of the Department of agronomical sciences of Biskra University in Southeast Algeria. Signiﬁcant variations in most of the traits were strikingly demonstrated using variance analysis and coefficients of variation and the number of modalities, frequencies and Shannon–Weaver diversity index (H′) values for the quantitative and qualitative characters respectively indicating the heterogeneity of the studied accessions. The correlations between the studied quantitative variables showed that the yield parameters were correlated with the variables related to the vegetative part of the plant. The first five PCs explained 76.877 % of the total variation and identified the most discriminant variables related particularly to yield and fruit characteristics contributing to PC1: fruit width; fruit index; fruit weight, number of locules; placenta length, pedicel length, anther length, leaf width and plant height /stem length ratio. For several qualitative traits, an important degree of variability was observed. The ﬁrst factorial dimension explained 42.5% of the variance and was mostly associated with: plant height; growth habit; flower position; corolla shape; number of flower per axil and fruit shape at pedicel attachment and at blossom end; calyx margin. Cluster analysis of the combined data grouped the pepper landraces into four clusters regardless of the localities and the closest accessions belonged to different localities and/or provinces. This study notably confirms the presence of considerable genetic diversity within and between accessions of hot pepper in Algeria and provides a basis for its active conservation and future selection to develop improved local pepper populations